Stigma as a Barrier to Substance Abuse Treatment Among Those With Unmet Need: An Analysis of Parenthood and Marital Status. (January 2018) - Stringer, Kristi L.; Baker, Elizabeth H.
Substance use (SU) stigma is one factor contributing to unmet need for SU treatment. Additionally, theory suggests that women and single parents who use substances experience enhanced stigma because they do not adhere to normative social expectations. This study examines differences in perceived stigma by gender and parenthood among those with unmet need for SU treatment using the 2003-2010 National Survey of Drug Use and Health ( N = 1, 474). Results indicate that women are more likely to report stigma as a barrier to treatment compared with men, though the interaction between gender and parenthood is not significant. We find that married parents report the highest level of stigma. We situate our findings in past health-related stigma research. We suggest that these results shed a light on stigma, particularly as it relates to family status, as a contributing factor to differences regarding SU treatment utilization. Finally, we raise a provocative question concerning social status and anticipated stigma.